The Effect of Admission Hypothermia for Neonatal Death Among Neonates Admitted to Neonatal Intensive Care Unit at Sheik Hassan Yabare Jigjiga University Referral Hospital in Jigjiga City, Somali Region, Eastern Ethiopia - Ibrahim AM; Farah AM; Osman MO; Hashi A (Dove Medical Press, 2021)
Ahmed Mohammed IbrahimAbdirahman Mahamed FarahMohamed Omar OsmanAbdiwahab Hashi Department of Public Health, College of Medicine and Health Science, Jigjiga University, Jigjiga, Ethiopia Correspondence: Ahmed Mohammed Ibrahim; Mohamed Omar OsmanDepartment of Public Health, College of Medicine and Health Science, Jigjiga University, P.O.Box: 1020, Jigjiga, EthiopiaTel +251 912423271; +251 921424748Fax +251 25 775 5976Email Ahmey114baba@gmail.com; Wehliye@jju.edu.et   Background: Hypothermia contributes to morbidity and mortality of newborns. While there have been improvements in neonatal mortality both globally and nationally, there are still important regional differences. Adopting prevention and intervention practices to reduce hypothermia at birth may help achieve the global and national goal of reducing neonatal mortality.Purpose: To assess the contribution of admission hypothermia to mortality among hospitalized newborn infants.Methods: Retrospective cohort study was conducted in Sheik Hassan Yabare Jigjiga University Referral Hospital. Neonates were admitted to the Neonatal Intensive Care Unit were selected by using simple-random sampling technique from record of neonates. Descriptive survival analysis such as Log rank test, life table and Kaplan–Meier survival curve and bivariate and multivariate inferential Cox regression were used to estimate hazard ratios with 95% confidence intervals.Results: Among 588 neonates, 146 (24.8%) died and 442 (75.2%) were censored. A total of 2509 days were followed for hypothermic neonates and 2337 days for normothermic neonates. The death rate was 37 per 1000 days and 22 per 1000 days for hypothermic and normothermic neonates, respectively. Survival function between the two groups differed significantly. Hypothermic neonates had a 59% (AHR: 1.59, CI: 1.1, 2.3) hazard of death than normothermic neonates. Not having initiated breastfeeding (AHR: 1.9, CI: 1.13, 3.1), vaginal mode of delivery (AHR: 0.68, CI: 0.5, 0.98), suspected sepsis (AHR: 1.5, CI: 1.06, 2.1), and respiratory distress (AHR: 2, CI: 1.44, 2.88) were significant predictors of neonatal death.Conclusion: The death rate for hospitalized, hypothermic neonates was greater than those who were normothermic. Hospitalized newborns should be monitored closely and hypothermia minimized. Management and guidelines to minimize hypothermia management practices should be rigorously evaluated in medical resource-limited settings. Keywords: effect, admission hypothermia, neonatal mortality, survival, NICU, SHYRH, Jigjiga, Ethiopia